2006
DOI: 10.1111/j.1471-4159.2006.04158.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of translation initiation and peptide chain elongation during BDNF‐induced LTP in vivo: evidence for compartment‐specific translation control

Abstract: Protein synthesis underlying activity-dependent synaptic plasticity is controlled at the level of mRNA translation. We examined the dynamics and spatial regulation of two key translation factors, eukaryotic initiation factor 4E (eIF4E) and elongation factor-2 (eEF2), during long-term potentiation (LTP) induced by local infusion of brain-derived neurotrophic factor (BDNF) into the dentate gyrus of anesthetized rats. BDNF-induced LTP led to rapid, transient phosphorylation of eIF4E and eEF2, and enhanced express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 52 publications
4
92
0
Order By: Relevance
“…This was later supported by results showing effects of BDNF on the translation machinery in dendrites of cultures cerebrocortical neurons (Takei et al, 2004) as well as in synaptoneurosome preparations (Kanhema et al, 2006;Takei et al, 2004). The effect of BDNF on the synaptic proteome was analyzed in more detail in synaptoneurosomes isolated from cultured cortical neurons, using multidimensional protein identification technology (MudPIT) and relative quantification by spectra counting.…”
Section: Bdnf-induced Changes In the Neuronal Proteomementioning
confidence: 88%
See 2 more Smart Citations
“…This was later supported by results showing effects of BDNF on the translation machinery in dendrites of cultures cerebrocortical neurons (Takei et al, 2004) as well as in synaptoneurosome preparations (Kanhema et al, 2006;Takei et al, 2004). The effect of BDNF on the synaptic proteome was analyzed in more detail in synaptoneurosomes isolated from cultured cortical neurons, using multidimensional protein identification technology (MudPIT) and relative quantification by spectra counting.…”
Section: Bdnf-induced Changes In the Neuronal Proteomementioning
confidence: 88%
“…A BDNF-induced increase in the phosphorylation of eIF4E, which is correlated with enhanced rates of translation (Gingras et al, 2004), was also observed in dentate gyrus (DG) following infusion of BDNF to induce LTP (BDNF-LTP) and in DG synaptoneurosomes stimulated with BDNF (Kanhema et al, 2006). Furthermore, BDNF infusion into the DG of anesthetized animals was found to increase eIF4E total protein levels, further suggesting that eIF4E upregulation induces local protein synthesis at the synapse, and may contribute to the effects of BDNF in synaptic potentiation.…”
Section: Bdnf and Regulation Of Translation Machinerymentioning
confidence: 94%
See 1 more Smart Citation
“…MEK inhibitors such as U0126 block ERK phosphorylation and attenuate early and late phase LTP in the CA1 region and dentate gyrus (7,25,28,33,34). Here, we investigated the effects of MEK-ERK signaling on dynamic changes in translation factor activity during in vivo LTP.…”
Section: Erk-dependent Regulation Of Initiation Factor Activity and Ementioning
confidence: 99%
“…Phosphorylation of eEF2 on Thr 56 inhibits eEF2-ribosome binding and arrests peptide chain elongation (21,22). Paradoxically, eEF2 is phosphorylated in protein synthesis-dependent forms of LTP and long term depres-sion (23)(24)(25), yet synthesis of several plasticity-related proteins, including Arc, is maintained.…”
mentioning
confidence: 99%